Jaws - Zanuck, Richard D.; Brown, David, 1916-2010.; Spielberg, Steven, 1946-; Gottlieb, Carl.; Benchley, Peter; Universal Pictures Corporation (Universal City, Calif. : Universal Home Video, 2000)
A man-eating shark causes havoc off the Long Island coast and three men join together to hunt and destroy it.
Widescreen.
Originally produced as motion picture in 1975.
Based on the novel by Peter Benchley.
"This special 25th anniversary collector's edition contains exclusive footage, interviews and behind-the- scenes material."
Special features: spotlight on location, deleted scenes and outtakes, Get out of the water! trivia game, shark world, production photos and storyboards, original theatrical trailers, screen saver.
Music, John Williams.
Keywords: Sharks -- Drama; Feature films